Spatial spillover of global value chain in eco-efficiency - Li, Xinran; Liu, Chengkun; Zhang, Zhe (Frontiers in Environmental Science, 2022)
With increasing participation in the global value chain (GVC), China's economy has gradually entered the middle and late stages of industrialization and vigorous urbanization. However, the accompanying problems such as low-quality economic growth, excessive consumption of resources, scarce energy supply and environmental pollution have also become major issues that social development has to solve. Therefore, based on estimating the comprehensive index of regional eco-efficiency, it is of great practical significance to clarify the impacts of GVC embeddedness and government environmental protection system on regional eco-efficiency. From the perspective of spatial spillover, this paper explores the spatial dependence of eco-efficiency between regions, and deeply analyzes the spatial spillover effect of regional GVC embeddedness to provide feasible solutions for China to actively achieve the goals of "carbon peak" and "carbon neutrality". It has been found that the deepening of GVC embeddedness can play a certain positive role in regional eco-efficiency; a region can not only improve its own eco-efficiency through traditional methods such as import and export, but also drive the improvement of eco-efficiency in other regions through spatial spillover.